2001–2021 Comparative Persistence of Oral Antipsychotics in Patients Initiating Treatment: Superiority of Clozapine in Time-to-Treatment Discontinuation - Parabiaghi, Alberto; Galbussera, Alessia A.; D’Avanzo, Barbara; Tettamanti, Mauro; Fortino, Ida; Barbato, Angelo (Pharmacopsychiatry, 2024)
Background Continuous antipsychotic (AP) therapy is crucial for managing psychotic disorders, and its early interruption reflects the drugʼs failure. Real-world epidemiological research is essential for confirming experimental data and generating new research hypotheses.Methods The persistence of oral APs in a large population sample from 2000 to 2021 was analyzed by comparing AP prescriptions over this period across four Italian provinces, using dispensing data linked via a record-linkage procedure among regional healthcare utilization databases. We calculated personalized daily dosages and assessed time-to-treatment discontinuation over a 3-month period for patients initiating AP treatment. Treatment persistence was evaluated using Kaplan-Meier curves and Cox regression, with adjustments for age and sex.Results Second-generation antipsychotics (SGAs) were favored over first-generation antipsychotics (FGAs), with olanzapine as the most prescribed. Within the study time frame, 42,434 individuals were prescribed a new continuous AP regimen. The analysis revealed 24 significant differences within 28 comparisons. As a class, SGAs demonstrated better treatment persistence than FGAs (HR: 0.76; 95%CI: 0.73, 0.79). Clozapine stood out for its superior persistence, surpassing all other SGAs, notably olanzapine (HR: 0.85; 95%CI: 0.79–0.91) and risperidone (HR: 0.80; 95%CI: 0.74–0.87). Olanzapine and aripiprazole showed better results than both risperidone and quetiapine. Quetiapine showed inferior 3-month persistence in all pairwise comparisons.Conclusion The study results provide insight into the performance dynamics among SGAs: clozapine, despite being one of the less frequently dispensed APs in our sample, emerged as a significant prescription choice. The significance of pharmacoepidemiological studies in complementing experimental findings is also underscored.
Keywords: antipsychotics; prescribing; schizophrenia; pharmacoepidemiology